Biosensor for antioxidant determination in herbal tea, Orthosiphon stamineus benth - Mohd Noor Ahmad; Kwan, Wei Yen; A.K.M. Shafiqul Islam; Zhari Ismail; Misni Surif (Gadjah Mada University, 2008)
Organized by Chemical Engineering Department, Gadjah Mada University, 4th - 5th December 2007 at Yogyakarta, Indonesia.